2011
DOI: 10.1007/s11033-011-1339-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an intronic cis-acting element in the human dopamine transporter gene

Abstract: The human dopamine transporter gene (hDAT) encodes the dopamine transporter in dopamine (DA) neurons to regulate DA transmission. hDAT expression varies significantly from neuron to neuron, and from individual to individual so that dysregulation of hDAT is related to many neuropsychiatric disorders. It is critical to identify hDAT-specific cis-acting elements that regulate the hDAT expression. Previous studies showed that hDAT Intron 1 displayed inhibitory activity for reporter gene expression. Here we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In the human neuroblastoma SK-N-AS cells which served as another model for DA neurons 22 , overexpression of pcDNA3.1 + HIVEP2 increased the HIVEP2 protein levels as determined by Western blotting (Fig. 3a), verifying both the cDNA clone and the anti-HIVEP2 sera.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…In the human neuroblastoma SK-N-AS cells which served as another model for DA neurons 22 , overexpression of pcDNA3.1 + HIVEP2 increased the HIVEP2 protein levels as determined by Western blotting (Fig. 3a), verifying both the cDNA clone and the anti-HIVEP2 sera.…”
Section: Resultssupporting
confidence: 53%
“…Previous study showed that the 121-bp of haplotype A, especially a 36 bp subfragment containing the HIVEP2 target “1”, displayed inhibitory activity only on the SV40 promoter 22 . It was an expectation that we would be able to clone a trans -repressor, instead of a trans -activator (HIVEP2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An electrophoretic mobility shifting assay was carried by using nuclear proteins extracted from SH-SY5Y cells, according to our previously published protocol [18,30]. Oligonucleotides used for annealing are listed in Table 1.…”
Section: Electrophoretic Mobility Shifting Assaymentioning
confidence: 99%
“…Luciferase (Luc) reporters SV40-A (pGL3-SV40-A-luc) and SV40-B (pGL3-SV40-B-luc) were constructed by directionally inserting 40 bp dsDNA oligo containing DNPi allele A or B in the middle of the oligo, after self-annealing the oligos carrying two restriction site ends, into Hind III/ Nco I sites of Promega’s pGL3 SV40 Promoter vector (Madison, WI, USA; see Supplementary Table 1 for a list of all nucleotides used in this study). Preparation of 7.9kb constructs has been described before[25]. 7.9kb-A (pGL3-hDAT7.9kb-A) and 7.9kb-B (pGL3-hDAT7.9kb-B) differed only by DNPi alleles and both covered a SLC6A3 promoter region (7.9kb) from 5,931bp upstream of transcription start site to 35 bp downstream of DNPi.…”
Section: Methodsmentioning
confidence: 99%